Evaluation and clinical use of an intraoral inferior alveolar nerve block in the horse. (29th January 2014) - Henry, T.; Pusterla, N.; Guedes, A. G. P.; Verstraete, F. J. M.
Summary: Reasons for performing study: Local anaesthesia is often required to facilitate invasive procedures in equine dental patients under standing sedation. Objectives: To show that an intraoral approach can be used to desensitise the inferior alveolar nerve in horses and report complications seen with this technique. Methods: The distance of the mandibular foramen from the distal (caudal) edge of the mandibular third molar tooth, rostral edge of the mandibular ramus and ventral margin of the mandible were measured in 26 adult equine skulls of various ages and breeds. Computed tomography (CT) was used to verify the placement of the local anaesthetic with a custom‐made device on 4 equine cadaver heads. The technique was applied in 43 clinical cases having procedures performed on the mandibular quadrants using the delivery device. Results: Computed tomography demonstrated that the intraoral approach provided deposition of the local anaesthetic at the mandibular foramen and anatomical localisation of mandibular foramen indicated that anaesthetic solution could be delivered with a 38 mm needle. Clinical patients to lerated invasive dental procedures following the inferior alveolar nerve block with a 5 ml dose of local anaesthetic, without evidence of self‐inflicted lingual trauma. Conclusions: The inferior alveolar nerve was successfully desensitised with the intraoral approach with minimal complications. The reduced volume of local anaesthetic and ability to deposit the local anaesthetic in close proximity to the nerve compared with an extraoral technique may decrease the complication of self‐inflicted lingual trauma.